2017
DOI: 10.1161/strokeaha.116.015019
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a Healthy Nordic Diet and Risk of Stroke

Abstract: Background and Purpose-Specific dietary patterns, including the Mediterranean diet, have been associated with stroke prevention. Our aim was to investigate whether adherence to a healthy Nordic diet, including fish, apples and pears, cabbages, root vegetables, rye bread, and oatmeal, was associated with risk of stroke. Methods-Incident cases of stroke among 55 338 men and women from the Danish Diet, Cancer and Health cohort were identified from the Danish National Patient Register and verified by review of rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 32 publications
1
50
0
3
Order By: Relevance
“…Sixteen prospective studies were included in the meta-analysis for consumption of whole grains (16 reports) (Del Gobbo et al 2015;Djousse and Gaziano 2007;Hansen et al 2017;Helnaes et al 2016;Jensen et al 2004;Liu et al 2000b;Liu et al 1999;Mizrahi et al 2009;Muraki et al 2015;Neelakantan et al 2016;Nettleton et al 2008;Rautiainen et al 2012;Sonestedt et al 2015;Steffen et al 2003;Tektonidis et al 2015Tektonidis et al , 2016 (Supplemental Table 2), 9 studies for refined grains (8 reports) (Djousse and Gaziano 2007;Eshak et al 2014;Liu et al 2000b;Mizrahi et al 2009;Muraki et al 2015;Sonestedt et al 2015;Steffen et al 2003;Yu et al 2013) (Supplemental Table 3), 35 for vegetables (32 reports) (Belin et al 2011a;Bendinelli et al 2011;Bhupathiraju et al 2013;Buckland et al 2009;Dauchet et al 2004;Del Gobbo et al 2015;Dilis et al 2012;Gillman et al 1995;Hansen et al 2017;Hansen et al 2010;Hirvonen et al 2001;Johnsen et al 2003;Joshipura et al 1999;Keli et al 1996;…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen prospective studies were included in the meta-analysis for consumption of whole grains (16 reports) (Del Gobbo et al 2015;Djousse and Gaziano 2007;Hansen et al 2017;Helnaes et al 2016;Jensen et al 2004;Liu et al 2000b;Liu et al 1999;Mizrahi et al 2009;Muraki et al 2015;Neelakantan et al 2016;Nettleton et al 2008;Rautiainen et al 2012;Sonestedt et al 2015;Steffen et al 2003;Tektonidis et al 2015Tektonidis et al , 2016 (Supplemental Table 2), 9 studies for refined grains (8 reports) (Djousse and Gaziano 2007;Eshak et al 2014;Liu et al 2000b;Mizrahi et al 2009;Muraki et al 2015;Sonestedt et al 2015;Steffen et al 2003;Yu et al 2013) (Supplemental Table 3), 35 for vegetables (32 reports) (Belin et al 2011a;Bendinelli et al 2011;Bhupathiraju et al 2013;Buckland et al 2009;Dauchet et al 2004;Del Gobbo et al 2015;Dilis et al 2012;Gillman et al 1995;Hansen et al 2017;Hansen et al 2010;Hirvonen et al 2001;Johnsen et al 2003;Joshipura et al 1999;Keli et al 1996;…”
Section: Resultsmentioning
confidence: 99%
“…The Nordic diet tries to reflect the diet consumed in Nordic countries, particularly its healthier choices, including the intake of apples, pears and berries, root and cruciferous vegetables as well as cabbages, whole grain and rye bread as cereals, high intake of fish, low-fat dairy products, potatoes and vegetable fats, among others [ 1 , 2 ]. To our knowledge, the long-term effects of the Nordic diet on major chronic diseases have only been investigated in prospective cohorts within Nordic countries (Denmark, Sweden, and Finland) [ 3 10 ] and the observed effects remain inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, epidemiological findings have suggested that accordance to the Mediterranean diet or healthy Nordic diet was inversely correlated with incident stroke. [ 4 , 5 ]…”
Section: Introductionmentioning
confidence: 99%